2015
DOI: 10.1039/c5ta01857a
|View full text |Cite
|
Sign up to set email alerts
|

Picolinic acid as an efficient tridentate anchoring group adsorbing at Lewis acid sites and Brønsted acid sites of the TiO2 surface in dye-sensitized solar cells

Abstract: Picolinic acid anchored dye JA2 onto the TiO 2 via tridentate mode, the JA2+TTR2 based-device showed the highest PCE of 8.98%.We developed a novel efficient tridentate anchoring group which can anchor dye onto the TiO 2 surface via synchronously choosing Lewis acid sites and Brønsted acid sites of the TiO 2 . With the purpose of comparing the traditional carboxylate anchoring group to picolinic acid, two new D-π-A porphyrin dyes (JA1 and JA2) differing only in anchoring groups have been synthesized and applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…10 More recently, DSSC small molecules relying on a triarylamine donor and RCN acceptor were developed [11][12][13] and have generated PCEs up to 8.98% for an optimized device using a Zn 2+ porphyrin co-sensitizer. 14 As interest in bulk-heterojunction (BHJ) devices increased, a plethora of small molecule (SM) donor materials relying on RCN appeared. 5,[15][16][17][18][19][20] A series of solution-processable SM donors were introduced, 2,21-23 each bearing terminal RCN acceptor groups along an oligothiophene backbone of varying repeat units.…”
Section: Introductionmentioning
confidence: 99%
“…10 More recently, DSSC small molecules relying on a triarylamine donor and RCN acceptor were developed [11][12][13] and have generated PCEs up to 8.98% for an optimized device using a Zn 2+ porphyrin co-sensitizer. 14 As interest in bulk-heterojunction (BHJ) devices increased, a plethora of small molecule (SM) donor materials relying on RCN appeared. 5,[15][16][17][18][19][20] A series of solution-processable SM donors were introduced, 2,21-23 each bearing terminal RCN acceptor groups along an oligothiophene backbone of varying repeat units.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng and co-workers reported two porphyrin dyes JA1 and JA2 by co-sensitizing with a y-shaped dye (TTR2, Figure22), which has an absorption maximum at 521 nm. [78] This report demonstrated that the IPCE action spectrum of the co-sensitized device enhanced between4 00-600nm, resulting in increased J SC of JA1 + TTR2 (13.42 mA cm À2 )a nd JA2 + TTR2 Figure 17. J-V characteristics and the corresponding IPCE spectra of devices made with LD12, CD5,and LD12 + CD5 with the same TiO 2 films (17 + 5mm) under 1sun AM 1.5 Girradiation.…”
Section: Effect Of Co-sensitizersi Nporphyrin Dyesmentioning
confidence: 76%
“…On the other hand, the anchoring groups of dyes can definitively influence the electron injection from the molecules into the conduction band (CB) of TiO 2 semiconductor . Recently, pyridine, 8‐hydroxylquinoline and picolinic acid have been reported as new anchoring groups in Zn‐porphyrin dyes . We have reported salicylic acids as tridentate anchoring groups for Zn‐porphyrin dyes that evidently augmented the efficiency of interfacial charge transfer .…”
Section: Introductionmentioning
confidence: 96%